Origin of postcollisional magmas and formation of porphyry Cu deposits in southern Tibet - Wang, R.; Weinberg, R.; Collins, Bill; Richards, J.; Zhu, D. (Elsevier BV, 2018)
The recent discovery of large porphyry copper deposits (PCDs) associated with Miocene (22–12 Ma) granitoid magmas in the eastern section of the Paleocene-Eocene Gangdese magmatic arc in the Himalaya-Tibetan orogenic belt raises new questions about the origin of water-rich (≥4.5 wt.%), oxidized (ΔFMQ 1–3) magmas in continental collisional settings and their mineralization potential. We review the literature and compile available data on whole rock and isotope geochemistry for Cenozoic igneous rocks from Tibet, and add new zircon Ce4+/Ce3+ and Ti-in-zircon thermometry data to better understand variations in oxidation state and thermal evolution of these suites, which are key controls on Cu mineralization. Six distinct Cenozoic igneous suites are defined: Paleocene-Eocene syn-collisional Gangdese magmatic arc rocks (ΔFMQ = −1.2 to +0.8) (suite I), and five broadly contemporaneous Miocene suites. A distinct change in magmatism along the length of the belt occurs at around 88°E in the Miocene suites: to the east, porphyry copper mineralization is associated with a moderately oxidized, high-Sr/Y granitoid suite (suite II, ΔFMQ = +0.8 to +2.9) with minor occurrences of transitional (hybrid) monzonitic (suite III) and trachytic rocks (suite IV; both with zircon Ce4+/Ce3+ > 50–100, EuN/EuN* = ~0.5, and ΔFMQ = ~+1 to +2). To the west of 88°E, trachytic volcanic rocks (suite V) are more voluminous but more reduced (zircon Ce4+/Ce3+ < 50, ΔFMQ < +1), and are associated with sparse, poorly mineralized high-Sr/Y granitoids (suite VI) which are moderately oxidized (zircon Ce4+/Ce3+ = 20–100, ΔFMQ = ~+1 to +3).